WEBUSE: Website Usability Evaluation Tool - Chiew, Thiam Kian; Salim, Siti Salwa (Malaysian Journal of Computer Science, 2003)
Usability is one of the major factors that determines the successfulness of a website. It is important therefore to have certain measurement methods to assess the usability of websites. The methods could be used to help website designers make their websites more usable. This research focuses on website usability issues and implements a tool for evaluating the usability of websites, called WEBUSE (WEBsite USability Evaluation Tool). Based on literature research, a 24-question evaluation questionnaire has been formulated. The questionnaire is implemented as a Web-based tool. Visitors’ of a website can use it to evaluate the usability of the website. The visitors’ responses to the questionnaire are analysed. The results of the analysis show the good and bad usability aspects of the website. Website designers and developers can improve their websites based on these results. WEBUSE is suitable for the evaluation of all types of websites. Evaluation provided by WEBUSE is reliable and has received favourable user satisfaction and acceptance.